2018
DOI: 10.3892/or.2018.6723
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol, a prenylated flavonoid from Hops, exerts anticancer effects against gastric cancer in�vitro

Abstract: Xanthohumol (Xn), a prenylated flavonoid isolated from Hops (Humulus lupulus L.), has demonstrated potent anticancer activity in multiple types of cancer. However, the effect of Xn on gastric cancer (GC) remains unknown. The aim of the present study was to investigate the effect of Xn on GC cell proliferation, apoptosis and metastasis. It was observed that Xn decreased the viability of GC cells, with very low or no toxicity to normal gastric epithelial cells GES-1 at a concentration of 1–100 µM. The proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…Recently, we documented excellent antiproliferative action of 1C acridine chalcone in HCT116 cells [11]. In the last decade, some articles indicated a relationship between the antiproliferative effect and induction of oxidative stress in both natural and synthetic chalcones [51][52][53][54]. This fact prompted us to evaluate the role of ROS/RNS in the antiproliferative and proapoptotic effect of chalcone 1C.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we documented excellent antiproliferative action of 1C acridine chalcone in HCT116 cells [11]. In the last decade, some articles indicated a relationship between the antiproliferative effect and induction of oxidative stress in both natural and synthetic chalcones [51][52][53][54]. This fact prompted us to evaluate the role of ROS/RNS in the antiproliferative and proapoptotic effect of chalcone 1C.…”
Section: Discussionmentioning
confidence: 99%
“…Choi and coauthors [36] reported the cytotoxic and apoptogenic potential of kaempferol against the colorectal cancer HCT116 cells through the enhancement in the generation of ROS. In a report by Wei and coworkers [37], it was found that xanthohumol, a prenylated flavonoid isolated from Humulus lupulus L. exhibited its antiproliferative and apoptotic effects by the overproduction of ROS in gastric cancer AGS cells. The loss of mitochondrial membrane permeability is another important feature for the determination of apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…both were able to reduce this parameter, but not to completely inhibit the secretion even at the highest To the best of our knowledge, this is the first study demonstrating the anti-inflammatory activity of xanthohumol D in human gastric epithelial cells. Many literature studies have investigated the biological properties of xanthohumol A, which is mostly known for its anti-proliferative activity in different cancer cell lines, including gastric cells (Wei et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In the second study, a high molecular weight fraction from hop bract extract, rich in polymerized catechins, reduced in mice the gastric damage induced by the oral administration of VacA, a vacuolating cytotoxin produced by Helicobacter pylori (Yahiro et al, 2005) (Yahiro et al, 2005) (Yahiro et al, 2005) (Yahiro et al, 2005). As anti-inflammatory effects, a CO2 hop extract reduced the prostaglandin E2 production in adenocarcinoma gastric cells (AGS) by influencing COX-2 enzyme (Tripp et al, 2005), while xanthohumol A suppressed the proliferation, apoptosis and metastasis of AGS cells via induction of ROS production and inhibition of the NF-κB signaling (Wei et al, 2018).…”
Section: Introductionmentioning
confidence: 99%